Social and Moral Practices of the Organizations and Employee-Based Brand Equity: Female Digital Labor Perspective - Hu, Sha (Frontiers in Psychology, 2022)
The present study investigated the role of how socially responsible management and organizational morality are significant factors in employee moral engagement, employee vitality, and employee based brand equity. HRM policies and strategies are important for addressing the interests of the employees and boosting the overall effectiveness of the organization. To examine this, the present study analyzed the role of socially responsible management and organizational morality on employee moral engagement with the mediation of employee vitality. Also, the study examined the role of employee moral engagement on employee based brand equity. To conduct this study, the data was obtained from 310 female employees working in software houses from home in China. PLS-SEM technique was used to analyze the data of the study. The study found that socially responsible management has an effect on both employee moral engagement and employee vitality. The study revealed that organizational morality has an effect on employee moral engagement and employee moral engagement has an impact on employee based brand equity. However, an insignificant relationship was found between organizational morality and employee vitality. The results of the mediation analysis showed that employee vitality mediates the relationship between socially responsible management and employee moral engagement. However, employee vitality did not mediate the relationship between organizational morality and employee moral engagement. The study provided practical implications explaining the strategies and policies that can be opted by the HR department of the organization to boost employee interests. The study also provided some limitations and future recommendations such as sample size, the context of the study, and adding new variables to the existing framework.